PELAKSANAAN KEWAJIBAN TERA ULANG DALAM UPAYA MEWUJUDKAN HUKUM PERLINDUNGAN KONSUMEN - NIM. A1011211202, FREDERICK YEREMIA SINAGA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Reverification is regulated under Law Number 2 of 1981 concerning Legal Metrology. Article 1 point (r) defines reverification as the periodic affixing of a valid verification mark or a void verification mark, carried out by authorized officials based on testing conducted on measuring, weighing, and auxiliary instruments. Reverification protects consumers from losses or fraud committed by traders. This research aims to understand and analyze the implementation of re-verification as an effort to realize Consumer Protection Law, as well as to identify and analyze the obstacles faced by the government in conducting re-verification. The research employs an empirical juridical method. The analysis is carried out descriptively to explain re-verification in the context of enforcing Consumer Protection Law. The data was obtained from both primary and secondary sources through observation, interviews, documentation, and legal regulations. A qualitative method is used to gain a comprehensive understanding of reverification efforts in supporting Consumer Protection Law. The results show that the implementation of verification and reverification has not been fully effective as stipulated in Law Number 2 of 1981 concerning Legal Metrology, which mandates that verification and re-verification must be conducted once a year. In this study, it was found that two weighing devices from two traders had not been re-verified. Furthermore, there are still buyers/consumers who suffer losses due to unverified or non-re-verified weighing devices. Based on interview results, six individuals have experienced losses due to inaccurate weighing instruments. This situation leads to the non-fulfillment of consumer rights as stipulated in Law Number 8 of 1999 concerning Consumer Protection, particularly Article 4 points (b), (c), and (h). The obstacles faced by the Legal Metrology Unit of Pontianak City include the lack of understanding among measuring instruments, weighers, and their accessories) owners that their equipment is required to be re-verified, causing some owners to be reluctant to comply. To address this, the Legal Metrology Unit of Pontianak City has conducted face-to-face outreach to market traders to explain the importance of reverification.The second obstacle is the absence of inspectors in the Legal Metrology Unit of Pontianak City, as mandated in Article 1 paragraph 11 of the Minister of Trade Regulation Number 26 of 2017. Keywords: Consumer Protection Law; Legal Metrology; Reverification Abstrak Tera ulang diatur dalam Undang-Undang Nomor 2 Tahun 1981 tentang Metrologi Legal. Pada pasal 1 butir r, tera ulang merupakan hak menandai berkala dengan tanda tera sah atau tanda tera batal yang berlaku dan dilakukan oleh pegawai-pegawai yang berhak melakukannya berdasarkan pengujian yang dijalankan atas alat ukur, takar, timbang, dan perlengkapannya. Tera ulang melindungi konsumen dari kerugian atau kecurangan yang dilakukan pedagang. Penelitian ini bertujuan untuk mengetahui dan menganalisis pelaksanaan tera ulang dalam upaya mewujudkan Hukum Perlindungan Konsumen serta untuk mengetahui dan menganalisis hambatan pemerintah dalam melakukan tera ulang. Penelitian ini menggunakan metode yuridis empiris. Analisis dilakukan secara deskriptif untuk menjelaskan tera ulang dalam upaya mewujudkan Hukum Perlindungan Konsumen. Data diperoleh dari data primer dan data sekunder yaitu observasi, wawancara, dokumentasi dan peraturan hukum. Metode kualitatif digunakan untuk memperoleh pemahaman mengenai tera ulang dalam upaya mewujudkan Hukum Perlindungan Konsumen. Hasil penelitian menunjukkan bahwa pelaksanaan tera dan tera ulang belum sepenuhnya berjalan dengan baik sebagaimana yang diatur dalam Undang-Undang Republik Indonesia Nomor 2 Tahun 1981 tentang Metrologi Legal yaitu kegiatan tera dan tera ulang dilakukan sekali dalam satu tahun. Dalam hal ini ditemukan 2 timbangan dari 2 pedagang yang belum ditera ulang, masih adanya pembeli/konsumen yang dirugikan akibat timbangan yang tidak sesuai atau belum ditera/tera ulang. Berdasarkan hasil wawancara, terdapat 6 orang yang pernah mengalami kerugian akibat timbangan yang tidak sesuai. Hal ini berdampak pada tidak terpenuhinya hak-hak konsumen yang diatur dalam Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen khususnya pada pasal 4 butir b, 4 butir c dan pasal 4 butir h. Hambatan bagi UPT Metrologi Legal Kota Pontianak yaitu adanya pemilik UTTP kurang memahami bahwa timbangan yang dimilikinya wajib dilakukan tera ulang, sehingga pemilik UTTP terkadang tidak mau melakukan tera ulang. Dalam hal ini, UPT Metrologi Legal sudah melakukan sosialisasi secara face to face kepada pedagang di pasar untuk memberikan penjelasan tentang tera ulang. Hambatan yang kedua yaitu tidak adanya pengawas di UPT Metrologi Legal Kota Pontianak sebagaimana yang telah diatur pada Peraturan Menteri Perdagangan Nomor 26 Tahun 2017 pasal 1 ayat 11. Kata kunci: Hukum Perlindungan Konsumen; Metrologi Legal; Tera Ulang